1973
DOI: 10.1172/jci107259
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sucrase, Enterokinase, and Peptide Hydrolase after Intestinal Resection THE ASSOCIATION OF CELLULAR HYPERPLASIA AND ADAPTATION

Abstract: A B S T R A C T In a study of changes in digestive enzymes after massive intestinal resection and the mechanisms by which such changes occur, rats were sacrificed 4 wk after removal of the proximal two-thirds of the small intestine. Alterations in the mucosal levels of sucrase, enterokinase, and dipeptide hydrolase (Lleucyl-L-alanine substrate) were examined in the light of associated changes in protein, DNA and wet mucosal weight, measured in standardized gut segments from various regions of intestine.Metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
1

Year Published

1977
1977
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 29 publications
1
37
1
1
Order By: Relevance
“…One of the interesting characteristics of the diets is that the diets are composed of simple or elemental form of nutrients which minimize the digestive process. The other is that the diets contain no indigestible bulk of fibrous materi als which leads to striking diminution in fecal excretion (15,17). All the diets used in the present study contained no cellulose component.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…One of the interesting characteristics of the diets is that the diets are composed of simple or elemental form of nutrients which minimize the digestive process. The other is that the diets contain no indigestible bulk of fibrous materi als which leads to striking diminution in fecal excretion (15,17). All the diets used in the present study contained no cellulose component.…”
Section: Discussionmentioning
confidence: 83%
“…McCARTHY and KIM (15) found in the proximally resected rats that significant elevation in fecal excretion occurred in the second postoperative week, falling towards normal by the fourth week. NYGAARD (11) reported with a laboratory chow containing 23% of crude protein and 2.6% of fat that fecal nitrogen excretion did not change by 25% distal resection, but increased progressively as the extent of small bowel resected was larger.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies have shown that rapid alterations in mucosal functions are observed in response to the composition of diet [1], fasting [2], total parenteral nutrition [3], intestinal resection [4], or diabetes mellitus [5,6]. However, the mechanisms regulating the adaptation of intestinal absorption are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of cytosol fraction. The cytosol fractions were obtained by the method of MacCarthy and Kim [ 11 ] from the intestinal mucosa at the same sites described above from rats fed experimental diets for 1 week or 1 month. The mucosa was homogenized in 14% glycerol and centrifuged (Type 70P-72, Rp55T rotor, Hitachi Koki Co., Tokyo) at 45,000 X g for 1 h at 0°C.…”
Section: Methodsmentioning
confidence: 99%